TERORISME DAN JIHAD DALAM PERSPEKTIF AL-QUR’AN - gonsales gonsales (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
Islam constantly calls for peace and togetherness, even condemning violence and terror. However, the charge against Islam as a terrorism ideology is a very heartbreaking thing for the (Muslim) community. However, it can not be denied that there is a tendency in understanding the Qur’an and hadith textually and literally an sich that can lead to behavior that seems anarchist, intolerant, and tend to destructive. Jihad teachings, for example, are often misunderstood as justification for actions and propaganda, radical acts, bombings and terrorism. Seeing the reality that happens, is a necessity to provide a correct understanding of Islam. As a first step, it is necessary to comprehend a comprehensive methodology in understanding nash. There is many discussions in the matter of terrorists and jihad, therefore it must be distinguished between the two with the real meaning in the perspective of the Quran. In this discussion, there will be limited issues to be discussed include the definition of terrorists and jihad, verses that are often misunderstood as justification of terrorism, and how the full point of view of the Quran related to terrorism.